PENYULUHAN PENTINGNYA PENDIDIKAN TERHADAP PENINGKATAN KUALITAS HIDUP DI DESA SUKAMULYA - Nurmalasari , Neneng; Shobahi, Abdul Mu’ti; Permatasari, Desi Intan; Nurhabibah, Wiwit; Masitoh, Imas (Belalek, 2023)
One of the factors causing changes in individuals and society is education. Education provides certain values for humans, especially in opening their minds and accepting new things and also how to think scientifically. Higher education institutions have contributed in overcoming development problems, especially in the field of education. Higher education institutions have demands to be one of the parties that bridge the development gap, especially the gap in the education sector. Based on the results of the implementation of Community Service activities, it can be concluded that Community Service activities "Counseling and Socialization of the Importance of Education for Humans in Sukamulya Village, Pangandaran Regency" namely community members are more motivated to improve their standard of living by continuing to continue their education to a higher level.